Factors Related to the Level of Health Literacy in Patients with Hypertension: Literature Review - Rezkisa Dwi Prambudia; Ika Yuni Widyawati; Eka Misbahatul Mar'ah Has (Critical Medical and Surgical Nursing Journal (CMSNJ), 2021)
Introduction: Hypertension is the leading cause of death worldwide. People with hypertension often receive health education about their health but cannot implement it. Patients with hypertension must be responsible for self-management related to the level of a person's health literacy, such as efforts that should they take so that the illness they suffer from is not getting worse. The aim of this study is to determine the factors related to the level of health literacy in hypertensive patients.Methods: Search for articles and journals conducted in the last ten years, from 2010-2020 and published on the internet using Scopus, Science Direct, ProQuest, Pubmed, Google Scholar, Portal Garuda, and SINTA by using chosen keyword adjusted to the Medical Subject Heading (MeSH) and Indonesian Thesaurus, namely, "factors", "health literacy", " After analysis and tabulation from some of the articles and journals, there are several factors related to the level of health literacy in hypertensive patients such as, education, age, job, income, knowledge, acculturation, self-management efficacy, HBPM (Home Blood Pressure Measurement), regular use of medicine, systolic blood pressure, health service access, health information access, and social support.Results: There are several factors related to the level of health literacy in patients with hypertension after analyzing journals or articles .. This study is expected to increase knowledge for nurses about the level of health literacy of hypertensive patients. acculturation, self-management efficacy, HBPM (Home Blood Pressure Measurement), regular use of medicine, systolic blood pressure, health service access, health information access, and social support. Discussion: There are several factors related to the level of health literacy in patients with hypertension after analyzing journals or articles .. This study is expected to increase knowledge for nurses about the level of health literacy of hypertensive patients. acculturation, self-management efficacy, HBPM (Home Blood Pressure Measurement), regular use of medicine, systolic blood pressure, health service access, health information access, and social support.Conclusion: There are several factors related to the level of health literacy in patients with hypertension after analyzing journals or articles. This study is expected to increase knowledge for nurses about the level of health literacy of hypertensive patients.